Clinicopathological and Prognostic Characteristics of Esophageal Spindle Cell Squamous Cell Carcinoma: An Analysis of 43 Patients in a Single Center - Li, Peng; Li, Yang; Zhang, Chao; Ling, Yi-Hong; Jin, Jie-Tian; Yun, Jing-Ping; Cai, Mu-Yan; Luo, Rong-Zhen (Frontiers in Oncology, 2021)
Objective: Oesophageal spindle cell squamous cell carcinoma (ESCSCC) is a distinct subtype of oesophageal carcinoma with unique morphologic and clinicopathologic features. This study aimed to characterize the clinicopathologic manifestations and postoperative prognostic factors of ESCSCC. Methods: In this study, 43 ESCSCC patients who underwent oesophagectomy at Sun Yat-sen University Cancer Center between January 2001 and December 2014 were identified. 200 patients with conventional squamous cell carcinoma during the same period were sampled as a control. Haematoxylin and eosin-stained slides and available data were reviewed, and pertinent clinicopathologic features were retrospectively analysed. Results: Among the ESCSCC patients, the median age was 60.5 years, with a male-to-female ratio of 2.58:1. The five-year disease-free survival and cancer-specific survival rates were 51.6% and 55.5%, respectively. In the univariate analysis, drinking abuse, tumour size, macroscopic type, perineural invasion, pT, preoperative blood white blood cell count, preoperative blood neutrophil count, and preoperative blood neutrophil to lymphocyte ratio were significantly correlated with the cancer-specific survival and disease-free survival of the ESCSCC patients. The multivariate analysis showed that macroscopic type, perineural invasion, preoperative blood neutrophil to lymphocyte ratio, tumour size, and pT were independent prognostic factors for cancer-specific survival or disease-free survival. Moreover, the combined prognostic model for cancer-specific survival (including macroscopic type, perineural invasion, and preoperative blood neutrophil to lymphocyte ratio), the combined prognostic model for disease-free survival (including macroscopic type, perineural invasion, and tumour size) significantly stratified patients according to risk (low, intermediate, and high) to predict cancer-specific survival , disease-free survival, respectively. In terms of esophageal conventional squamous cell carcinoma cohort, there was no significant difference in long-term outcome when compared with ESCSCC. Though five independent prognostic variables (macroscopic type, perineural invasion, preoperative blood neutrophil to lymphocyte ratio, tumour size, and pT) were indentified in ESCSCC, univariate analysis demonstrated that perineural invasion, preoperative blood neutrophil to lymphocyte ratio were correlated with esophageal conventional squamous cell carcinoma on cancer-specific survival; whereas only perineural invasion on disease-free survival. Conclusions: The proposed two new prognostic models might aid in risk stratification and personalized management for patients with oesophageal spindle cell squamous cell carcinoma who received radical surgery.